Cobalt and zinc halide complexes of 4-chloro and 4-methylaniline: Syntheses, structures and magnetic behavior. (1st August 2019) - Chellali, Jonathan E.; Keely, Cailyn; Bell, Graham; Dimanno, Kimberly L.; Tran, Tran; Landee, Christopher P.; Dickie, Diane A.; Rademeyer, Melanie; Turnbull, Mark M.; Xiao, Fan
Graphical abstract: Reaction of Co(II) and Zn(II) halides with 4-chloro and 4-methylaniline produced an isocoordinate family of compounds. The Co(II) compounds exhibit antiferromagnetic interactions. Abstract: A family of cobalt(II) and zinc(II) compounds with the general formula (4-subC6 H4 NH2 )2 MX2, (M = Co, Zn; X = Cl, Br; sub = CH3, Cl) has been prepared and the compounds characterized by single-crystal X-ray diffraction. The eight compounds crystallize in the monoclinic space group I 2/a and are isocoordinate, but show different crystal packing for the 4-methyl and 4-chloroaniline complexes as a result of halogen bonding in the 4-chloroaniline family. The cobalt complexes have also been studied via variable temperature magnetic susceptibility measurements. All four Co(II) compounds exhibit antiferromagnetic exchange (maxima in χ are observed) and have been fitted with a 1D-chain model (cobalt chloride complexes, J  ∼ −3 K) or a 2D-model (cobalt bromide complexes, J  ∼ −4 K). Analysis of potential superexchange pathways is provided.